PENGARUH MUTUAL COUPLING PADA BEAMFORMING ANTENA ARRAY - Naufal Widya Gaspura; Dharu Arseno; Alloysius Adya Pramudita (TEKTRIKA, 2020)
In the antenna array there is a mutual coupling effect. Mutual coupling causes a decrease in the characteristics of the antenna parameters. In this study, an analysis of the effect of mutual coupling on beamforming results was carried out. In this study, it was concluded that the effect of mutual coupling depends on the distance between the antenna elements. In the simulation for the beam pointing to 60 degrees, at a distance of lambda the resulting beam is shifted by 70%. Distance of 12 lambda, beam shifted 25% to 45 degrees. At 3 4 lambda distance, the beam is close to the desired result direction, 64 degrees to be precise, at the lambda distance there is a grating lobe effect. In the end, it was found that mutual coupling affects the beam direction which causes the antenna radiation pattern to change.